KONSUMSI BUAH-SAYUR PADA SISWA SMA NEGERI 81 JAKARTA [THE CONSUMPTION OF FRUITS AND VEGETABLES AMONG STUDENTS OF SMA NEGERI 81 JAKARTA] - Aufa Hanifa; Kusharisupeni Djokosujono; Triyanti Triyanti; Salimar Salimar (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2020)
ABSTRACT Lack of fruit and vegetable consumption may increase the risk of non-communicable diseases in later life. Consumption of fruits and vegetables in the Indonesian population is still low, especially among adolescents. The study aimed to determine the dominant factor associated with fruit and vegetable consumption among high school students in SMA Negeri 81 Jakarta. This study used a cross-sectional study design and was conducted from March until April 2020, wich consist 143 respondents. Data collection including consumption of fruits and vegetables, gender, preferences, knowledge of fruits and vegetables, parental influence, peer influence, availability of fruits and vegetables at home, consumption of fast food, consumption of SSBs, pocket money, exposure to mass media, and parental education levels were carried out online. Data were analyzed by bivariate analysis with the Chi-Square test and multivariate analysis with multiple logistic regression tests. The results found that 67,1 percent of respondents consumed less fruit and vegetables (<400 grams per day). Bivariate results showed a significant relationship between gender, preference, parental influence, fruit and vegetable availability at home, and mass media exposure with fruit and vegetable consumption. Logistic regression analysis showed that the availability of fruits and vegetables at home was a dominant factor associated with fruit and vegetable consumption (OR = 5,8; CI = 1,7 – 20,3). The availability of fruits and vegetables at home was the dominant factor in the consumption of fruits and vegetables among students of SMA Negeri 81 Jakarta. It is necessary to implement policies that promote and provide easy access to fruits and vegetables through school and home to increase fruit and vegetable intake in adolescents. ABSTRAK Kurang konsumsi buah dan sayur dapat meningkatkan risiko terjadinya penyakit tidak menular di kemudian hari. Konsumsi buah dan sayur penduduk Indonesia masih rendah, terutama pada kalangan remaja. Tujuan penelitian untuk mengetahui faktor dominan konsumsi buah dan sayur pada siswa SMA Negeri 81 Jakarta. Desain penelitian cross-sectional, dilaksanakan pada bulan Maret hingga April 2020 dengan responden sejumlah 143. Data yang dikumpulkan meliputi konsumsi buah dan sayur, jenis kelamin, preferensi, pengetahuan tentang buah dan sayur, pengaruh orang tua, pengaruh teman sebaya, ketersediaan buah dan sayur di rumah, konsumsi fast food, konsumsi SSBs, uang jajan, keterpaparan terhadap media massa, dan tingkat pendidikan orang tua dilakukan secara daring. Data dianalisis secara bivariat dengan uji Chi-Square, dan analisis multivariat dengan uji regresi logistik ganda. Hasil penelitian menemukan sebanyak 67,1 persen responden kurang mengonsumsi buah dan sayur (<400 gram/hari). Hasil bivariat menunjukkan adanya hubungan yang signifikan antara jenis kelamin, preferensi, pengaruh orang tua, ketersediaan buah dan sayur di rumah, dan keterpaparan terhadap media massa dengan konsumsi buah dan sayur. Analisis regresi logistik menunjukkan bahwa ketersediaan buah dan sayur di rumah merupakan faktor dominan yang berhubungan dengan konsumsi buah dan sayur (OR = 5,8; CI = 1,7 – 20,3). Ketersediaan buah dan sayur di rumah merupakan faktor dominan konsumsi buah dan sayur pada siswa SMA Negeri 81 Jakarta. Perlu kebijakan untuk mempromosikan dan memberikan kemudahan akses konsumsi buah dan sayur melalui sekolah dan rumah untuk meningkatkan asupan buah dan sayur pada remaja.